The tailless gecko gets the worm: prey type alters the effects of caudal autotomy on prey capture and subjugation kinematics - Vollin, Marina F.; Higham, Timothy E. (Frontiers in Behavioral Neuroscience, 2023)
Prey capture and subjugation are complex behaviors affected by to many factors including physiological and behavioral traits of both the predator and the prey. The western banded gecko (Coleonyx variegatus) is a small generalist predator that consumes both evasive prey items, such as spiders, wasps, and orthopterans, and non-evasive prey items, including larvae, pupae, and isopterans. When consuming certain prey (e.g. scorpions), banded geckos will capture and then rapidly oscillate, or shake, their head and anterior part of their body. Banded geckos also have large, active tails that can account for over 20% of their body weight and can be voluntarily severed through the process of caudal autotomy. However, how autotomy influences prey capture behavior in geckos is poorly understood. Using high-speed 3D videography, we studied the effects of both prey type (mealworms and crickets) and tail autotomy on prey capture and subjugation performance in banded geckos. Performance metrics included maximum velocity and distance of prey capture, as well as velocity and frequency of post-capture shaking. Maximum velocity and distance of prey capture were lower for mealworms than crickets regardless of tail state. However, after autotomy, maximum velocity significantly increased for strikes on mealworms but decreased for crickets. After capture, geckos always shook mealworms, but never crickets. The frequency of shaking mealworms decreased after autotomy and additional qualitative differences were observed. Our results highlight the complex and interactive effects of prey type and caudal autotomy on prey capture biomechanics.